The Role of Interfaith Law and Policy in Managing Human Resources: Addressing Religious Diversity in the Workplace - Tjokro, Gunawan; Zaenuri, Zaenuri; Yanto , Heri; Rokhman, Fathur; Rajagukguk , Abdul; Ezzerouali , Souad (Universitas Negeri Semarang, 2025)
The increasing religious diversity in Indonesia poses significant challenges to human resource (HR) management in the workplace. This paper explores the role of interfaith law in addressing these challenges and promoting inclusivity in the Indonesian workplace. The novelty of this study lies in its focus on the intersection of religious diversity and HR management within the legal framework of Indonesia, particularly through the lens of interfaith law. By examining the current legal provisions and practices surrounding religious rights and freedoms, the paper underscores the critical role that interfaith law plays in creating an environment where employees from diverse religious backgrounds can coexist harmoniously. The urgency of addressing religious diversity in HR management is highlighted by the potential risks of discrimination, conflict, and marginalization, which can negatively impact organizational performance and employee well-being. With Indonesia being a predominantly Muslim country, but home to various other religious communities, the challenge of balancing religious rights and organizational goals remains ever-present. This paper contributes to the growing body of literature on diversity management by proposing legal frameworks and HR practices that not only comply with religious laws but also enhance organizational effectiveness. The findings call for more robust policies that integrate interfaith principles to manage religious diversity effectively, ensuring equitable treatment of all employees and fostering an inclusive workplace culture. By addressing the gaps in existing HR strategies, this study offers valuable insights for practitioners, policymakers, and scholars in managing religious diversity in Indonesia's dynamic workplace environment.